2022
DOI: 10.1002/alz.066868
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory dysfunction but not COVID‐19 severity predicts severity of cognitive sequelae following SARS‐CoV‐2 infection in Amerindian older adults

Abstract: Background COVID‐19 has affected more than 380 million people. Infections may result in long term sequelae, including neuropsychiatric symptoms. In older adults COVID‐19 sequelae resemble early Alzheimer’s disease, and may share risk factors and blood biomarkers with it. The Alzheimer’s Association Consortium on Chronic Neuropsychiatric Sequelae of SARS‐CoV‐2 infection (CNS SC2) established harmonized definitions, ascertainment and assessment methodologies to evaluate and longitudinally follow up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The fact that the elderly disproportionately develop severe COVID and long COVID raises the concern that olfactory impairment associated with COVID may increase the population's risk for Alzheimer’s disease. At the 2022 Alzheimer’s Association International Conference Gonzales-Aleman et al presented data from 766 Amerindian participants that demonstrated better prediction of cognitive impairment following COVID infection from severity of anosmia than from clinical status ( Gonzales-Aleman et al 2022 ). A study by Wang et al (2022) using electronic health records of both inpatient and outpatient visits between 2/2020 and 5/2021, revealed a significant increase in new-onset AD within 360 days after initial COVID diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the elderly disproportionately develop severe COVID and long COVID raises the concern that olfactory impairment associated with COVID may increase the population's risk for Alzheimer’s disease. At the 2022 Alzheimer’s Association International Conference Gonzales-Aleman et al presented data from 766 Amerindian participants that demonstrated better prediction of cognitive impairment following COVID infection from severity of anosmia than from clinical status ( Gonzales-Aleman et al 2022 ). A study by Wang et al (2022) using electronic health records of both inpatient and outpatient visits between 2/2020 and 5/2021, revealed a significant increase in new-onset AD within 360 days after initial COVID diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In our model, IFN-I dysregulation occurs in the setting of peripheral infection and is communicated centrally via sites such as the olfactory bulb, the brainstem nuclei and the blood–brain barrier ( Meinhardt et al, 2021 ; Krasemann et al, 2022 ). Sites specifically vulnerable to dysregulated IFN-I such as the olfactory bulb and the hippocampus ( Bayat et al, 2022 ; Stępień et al, 2023 ) may furthermore readily account for both clinical ( Gonzalez-Aleman et al, 2022 ) and neuropathological ( Lou et al, 2021 ) manifestations of the CNS involvement in COVID-19.…”
Section: Type I Interferon Signaling Dysregulation In the Brain Is A ...mentioning
confidence: 99%
“…In our model, IFN-I dysregulation occurs in the setting of peripheral infection and is communicated centrally via sites such as the olfactory bulb, the brainstem nuclei and the blood-brain barrier (Meinhardt et al, 2021;Krasemann et al, 2022). Sites specifically vulnerable to dysregulated IFN-I such as the olfactory bulb and the hippocampus (Bayat et al, 2022;Stępień et al, 2023) may furthermore readily account for both clinical (Gonzalez-Aleman et al, 2022) and neuropathological (Lou et al, 2021) manifestations of the CNS involvement in COVID-19. The generation of amyloid-beta and hyperphosphorylated tau, molecules that we currently recognize as inducers of innate immunity (Rexach et al, 2020;Roy et al, 2020;Jin et al, 2021;Roy et al, 2022;Vavougios et al, 2022a;Udeochu et al, 2023), can in turn sustain pathogenic IFN-I in a feed-forward manner acting as danger associated molecular pattern (Asai et al, 2015;Bolós et al, 2016) in a process that has been shown to prime microglia towards phenotypes specifically associated with the earlier stages of neurodegenerative disease (Roy et al, 2020;Jin et al, 2021;Magusali et al, 2021;Udeochu et al, 2023).…”
Section: Tonic Type I Interferon Signaling Dysregulation As a Shared ...mentioning
confidence: 99%